Carbon felt modified with bismuth and asphalt-derived carbon as a high-performance electrode for vanadium redox flow batteries - ZHI-CHEN ZHOU (PLoS ONE, 2025)
Vanadium redox flow batteries (VRFBs) are among the most promising large-scale energy storage systems, owing to high efficiency, scalability, and long cycle life. However, their widespread adoption is often hindered by sluggish electrode reaction kinetics, particularly at the anode. This investigation aimed to address these limitations by introducing bismuth-doped carbon (Bi/C) nanoparticles synthesized from asphalt and bismuth onto thermally treated carbon felt (TCF) to prepare Bi and C co-deposited thermally treated carbon felt (Bi/C-TCF), leveraging the synergistic effects between the two components. The synthesis process involved spray drying followed by high-temperature calcination, resulting in a highly efficient electrocatalyst for the V3+/V2+ redox couple. Electrochemical testing revealed that the Bi/C-TCF electrode significantly outperformed the conventional TCF electrode, exhibiting reduced polarization during charge-discharge cycles and enhanced catalytic activity as evidenced by its superior reaction rate constants K0 (2.37 × 10−2 and 2.75 × 10−2 cm/s) compared to TCF (2.08 × 10−2 and 2.10 × 10−2 cm/s). In single-cell tests, the Bi/C-TCF electrode, used as the negative electrode, demonstrated superior voltage efficiency (VE) and energy efficiency (EE) across various current densities. It achieved a power density of up to 1054.3 mW/cm2, significantly outperforming TCF’s 825.9 mW/cm2. After 1000 cycles, the VE and EE remained stable at 86.2% and 85.0%, respectively, whereas the TCF cell saw a rapid decline in VE and EE to below 70% after just 515 cycles. These findings highlight the potential of Bi/C nanoparticles as a scalable and cost-effective solution for enhancing the performance and durability of VRFBs, leveraging low-cost raw materials such as asphalt.